Integration of Students' Character Education Through Extracurricular Programs A Systematic Review - Nufa, Nurul Faizatin; Istichomahwati (Generate Digital Publishing, 2025)
Objective: This study aims to explore the significant relationship between students' participation in extracurricular activities and character development, while identifying key internal and external factors that influence the effectiveness of these activities in schools. Research Design & Methods: This study used a systematic literature review approach to identify, examine, and comprehensively analyze the relationship between extracurricular activities and character education as well as the factors that influence student participation, with the main data sources from journals and proceedings between 2020-2023 that were systematically selected using the PRISMA method. Findings: The study found that active involvement in extracurricular activities contributes significantly to instilling positive values such as social justice, self-esteem, self-confidence, and citizenship. It also enhances students' intellectual skills, teamwork, and engagement in the school community. The success of extracurricular programs relies heavily on quality internal management, a supportive school environment, and active student participation, as well as external support from parents, adequate facilities, and manageable scheduling. Implications & Recommendations: Schools should prioritize well-structured extracurricular programs that foster holistic character education, ensuring sufficient resources and parental involvement. Policy makers and educators are encouraged to view extracurricular activities as an essential component of education, rather than a supplement, to support students' academic success and social-emotional development. Contribution & Value Added: This study highlights the integral role of extracurricular activities in character education and provides a comprehensive framework for understanding the factors that maximize their effectiveness, offering practical insights for educators and school administrators aiming to enhance students' holistic development.